Understanding Revenge Pornography: A National Survey of Police Officers and Staff in England and Wales - Bond, Emma (Journal of interpersonal violence, 2021)
Online abuse, facilitated via social media and mobile technologies, has recently attracted considerable academic attention. The nonconsensual sharing of intimate images—revenge pornography—can have a devastating effect on victims, is a global problem, and constitutes interpersonal violence. The national helpline in the United Kingdom has now received over 7,000 calls. In the United Kingdom, new legislation making revenge pornography a crime was introduced in 2014, yet the police do not always respond appropriately to victims. This article presents the findings of a national online survey of police understanding of revenge pornography, undertaken in the United Kingdom in March 2017. The study set out to investigate police knowledge of revenge pornography legislation, their confidence in responding to cases of revenge pornography, and what level of training they had received. A total of 783 members of the police force responded to the survey and, to the authors’ knowledge, this the first study to seek to quantify the understanding of revenge pornography by police officers and staff in England and Wales. The findings suggest that the police in the United Kingdom have a limited understanding of revenge pornography legislation and lack confidence both in investigating cases and in effectively responding to victims. The implications of the study demonstrate that there is an urgent need for training across police forces to ensure that cases of revenge pornography are appropriately responded to, victims are safeguarded, and offenders brought to justice.